How Do You Solve For y For The Equation 2x–3y = 6?
Let us find the value of the variable y in the given equation 2x - 3y = 6
Answer: To solve for y for the equation 2x – 3y = 6, we will need to shift y to one side of the equation.
We take the term 3y to the right-hand side of the equation which gives 2x = 6 + 3y
Now we bring 6 to the left side of the equation 2x - 6 = 3y
And lastly, we bring the 3 also to the other side of the equation thus dividing the term (2x-6) by 3 which ultimately gives us the value of y.
(2x - 6) /3 = y